ADOPTION OF CIRCULAR ECONOMY PRINCIPLES IN NIGERIA CONSTRUCTION INDUSTRY (IJOVTECH, 2026)
Construction industry in Nigeria as one of the main industries that play a huge role in the national economy is also under increasing problems concerning resource depletion, waste creation as well as environmental degradation. This paper explores the use of the concept of the circular economy in the construction sector in Nigeria with a focus On approaches to waste minimization, resource utilization, and sustainability. Basing its study on a mixed-method, the study combines an extensive review of literature and a first hand data investigation including questionnaires and interviews with 250 construction professionals working in the main cities of Nigeria amongst which Lagos, Abuja, and Port Harcourt are found. The age of the participants can be grouped as 25-55 years (majority), the demography indicates that the participants are mostly men (78%), and the employment experience is 12 years on average. The main findings reveal that awareness is low (45 percent of participants are knowledgeable about the notion of the circular economy) and obstacles, including the poor regulatory environment, very expensive start-up costs, and insufficient technological infrastructure. But there is a chance in the digital tool such as digital twins and building information modeling that would be beneficial in increasing material reuse and recycles. The theoretical framework of the study is the circular economy model developed by the Ellen MacArthur Foundation; it is modified to the situation in Nigeria. Statistical analysis results such as chi-square tests reveal that there are significant agreements between levels of education and willingness to adopt (p < 0.05). The approaches that have been proposed include policy curterns, capacity building, and incentives towards steps towards the circular. The present study enhances the research topics in civil engineering by offering empirical data regarding a developing country viewpoint, and agreeing that circular economy potentially results in decreasing building waste by 30% in Nigeria, in accordance with the sustainability objectives on the planetary level such as United Nations Sustainable Development Goals. The results highlight the significance of the stakeholders that are involved to change the linear to the circular in construction.